Colorado 1870-2000 II Historical Landscape Photography - Jackson, William Henry 1843-1942; Fielder, John; Klucas, Gillian; Colorado Historical Society (Silverthorne, CO John Fielder Publishing, 2011)
This is volume II of the Jackson/Fielder project with 110 new comparison photo pair. Volumes I and II together represent the entire project in which the historic images of early west photographer William Henry Jackson capture a Colorado landscape both pristine and already dramatically affected by the onslaught on western civilization. Standing exactly where Jackson stood, and pointing his own camera in precisely the same direction, John Fielder has rephotographed Jackson's Colorado images to capture the often startling change that has occurred over the last century. The result is both breathtaking and stark, hopeful and disquieting. John Fielder describes the profound experience of traveling the state and seeing the landscape from Jackson's perspective, and reflects upon changes of the last 130 years.
Originally published: Englewood, Colo. : Westfield Publishers in cooperation with the Colorado Historical Society, 2005.
113849
Keywords: Wilderness areas; Landscape photography; Ecology; Colorado; History; Pictorial works